Adherence to COPD treatment: Myth and reality. (August 2017) - Rogliani, Paola; Ora, Josuel; Puxeddu, Ermanno; Matera, Maria Gabriella; Cazzola, Mario
Abstract: COPD is a chronic disease in which effective management requires long-term adherence to pharmacotherapies but the level of adhesion to the prescribed medications is very low and this has a negative influence on outcomes. There are several approaches to detect non-adherence, such as pharmacy refill methods, electronic monitoring, and self-report measures, but they are all burdened with important limitations. Medication adherence in COPD is multifactorial and is affected by patients (health beliefs, cognitive abilities, self-efficacy, comorbidities, psychological profile, conscientiousness), physicians (method of administration, dosing regimen, polypharmacy, side effects), and society (patient-prescriber relationship, social support, access to medication, device training, follow-up). Patient-health care professional communication, especially that between patient and physician or pharmacist, is central to optimizing patient adherence. However, the most realistic approach is to keep in mind that non-adherence is always possible, indeed, probable. Highlights: The level of medication adherence in COPD patients is very low. Approaches to assess adherence of COPD are burdened with important limitations. Patient views on therapy effectiveness are powerful predictors of reported adherence. The physician can affect adherence in COPD with his/her prescription. In COPD, adherence to inhalation medication is device-related.